2018
DOI: 10.1016/j.bja.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the QoR-15 score, a patient- reported outcome measure measuring quality of recovery after surgery and anaesthesia

Abstract: The QoR-15 fulfils requirements for outcome measurement instruments in clinical trials and is the first measurement instrument of postoperative quality of recovery to undergo a systematic review according to the COSMIN checklist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
171
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(189 citation statements)
references
References 29 publications
7
171
2
9
Order By: Relevance
“…[16][17][18][19] In a recent systematic review, the QoR-15 fulfilled the requirements for a patient-reported outcome questionnaire in the assessment of postoperative quality of recovery. 20 The province of KwaZulu Natal hosts the second largest population in South Africa and has an adult literacy rate of above There was no statistically significant difference in total QoR-15 scores and the VAS scores between male and female patients for both the English and isiZulu questionnaires. This was an interesting finding as previous studies reported worse postoperative quality of recovery scores for female patients when compared with their male counterparts.…”
Section: Patient Commentsmentioning
confidence: 89%
“…[16][17][18][19] In a recent systematic review, the QoR-15 fulfilled the requirements for a patient-reported outcome questionnaire in the assessment of postoperative quality of recovery. 20 The province of KwaZulu Natal hosts the second largest population in South Africa and has an adult literacy rate of above There was no statistically significant difference in total QoR-15 scores and the VAS scores between male and female patients for both the English and isiZulu questionnaires. This was an interesting finding as previous studies reported worse postoperative quality of recovery scores for female patients when compared with their male counterparts.…”
Section: Patient Commentsmentioning
confidence: 89%
“…In addition, patient-reported outcome measures (PROM) are increasingly relevant to health care providers and will influence clinical choices [ 5 ]. We have therefore undertaken a new exhaustive and comprehensive literature review representing a wide spectrum of clinical applications on key parameters relevant to patient outcome, in particular the influence of choice of anaesthetic technique on post-operative nausea and vomiting (PONV) [ 6 ]. Potential confounders and bias were minimised by strict adherence to Cochrane guidelines [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have made use of a bifactor model in outcome assessment, especially in mental health and quality of life research [7][8][9][10][11][12][13][14]. To our knowledge, only Kleif et al applied a bifactor model to a surgical population [15]. An analysis using the bifactor model may have the potential to establish an overall domain score, potentially resulting in the aforementioned advantages.…”
Section: Introductionmentioning
confidence: 99%